Perancangan Aplikasi Monitoring Bimbingan Tugas Akhir dengan Menggunakan Metode Agile di Perguruan Tinggi - Hendri (Jurnal PROCESSOR, 2024)
Thesis advisory is an essential process in students' academic journey; however, issues often arise during its implementation, such as the forgery of the advisor's signature and the advisors being unaware of the progress of the thesis.This study aims to investigate the implementation of the Agile methodology in the context of information system development, with a specific focus on the final thesis advisory process within higher education institutions. The Agile methodology, with its iterative approach and active involvement of relevant stakeholders, can provide greater flexibility in dealing with changing requirements, which often arise in the final thesis advisory process. Furthermore, this methodology enables the creation of sustainable information systems and improved testing, which are essential elements in ensuring higher quality and user satisfaction. This research involves an analysis of the enhancement of student thesis monitoring in the higher education environment. The results of this study are expected to provide valuable insights for higher education institutions looking to improve their final thesis advisory processes by leveraging the Agile approach in information system development. Additionally, this research may contribute to a deeper understanding of the effectiveness of the Agile methodology in the higher education environment, aiming to improve efficiency, quality, and satisfaction among users, including program heads, faculty, and students in the final thesis advisory process.